Origo Vitae: Um diálogo intertextual entre Haroldo de Campos e Gustave Courbet - Massagli, Sérgio Roberto [UNESP] (My University, 2007)
This work intends to undertake a comparative reading of two works of two different artists: The painting The Origin of the World by Gustave Courbet and the poem Origo Vitae by Haroldo de Campos and, from this reading, to verify how the border between the visible and the invisible may vanish and how, in a process of transcodifying, one mirrors the other in a dialogue that, besides surpassing different codes and times, produces new meanings and elicits a conversation about the act of reading these different codes.

O presente trabalho busca fazer uma leitura comparativa de duas obras de dois artistas diferentes: a tela intitulada “A Origem do Mundo”, de Gustave Courbet, e o poema “Origo Vitae”, de Haroldo de Campos e, a partir dessa leitura, constatar como a fronteira entre o visível e o legível pode se diluir, e como, num processo de transcodificação, um estabelece com o outro um diálogo que, além de transpassar os códigos e épocas, produz novos sentidos e suscita uma discussão sobre o ato da leitura destes diferentes códigos.
Origo Vitae: An intertextual dialogue between Haroldo de Campos and Courbet
Keywords: Intertextuality; Painting; Poetry; Reading